PENINGKATAN PENGETAHUAN PENTINGNYA SERTIFIKASI HALAL SEBAGAI STRATEGI PENINGKATAN DAYA SAING UMKM DI KABUPATEN BANJARNEGARA - Pujiyanto, M. Aris; Setyorini, Fitri Adi (Abdimas Awang Long, 2024)
This journal discusses efforts to increase knowledge about the importance of halal certification as a strategy to improve the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Banjarnegara Regency. Halal certification is a key factor in expanding market access and increasing consumer confidence. The purpose of this study is to improve the understanding of MSME groups in Banjarnegara Regency regarding the basic concepts of halal certification, its significance in the context of business competitiveness, and its positive impact on local economic growth. The knowledge improvement method involves socialization activities and workshops directly to MSME groups. The results are expected to have a positive impact on increasing awareness and implementation of halal certification among MSMEs, which in turn will contribute to increasing the competitiveness and economic growth of Banjarnegara Regency.